Axial strain imaging of intravascular data: results on polyvinyl alcohol cryogel phantoms and carotid artery - Brusseau, E; Fromageau, J; Finet, G; Delachartre, P; Vray, D (Ultrasound in medicine & biology, 2001)
Mapping the local elastic properties of an atherosclerotic artery is of major interest for predicting the disease evolution or an intervention outcome. These properties can be investigated by elastography, which estimates the strain distribution within a medium in response to a stress. But because diseased arteries are highly heterogeneous, a small global deformation may result in high local strains in the softest regions. For those reasons, we use in this paper the strain estimation method we recently developed to compute elastograms of original vessel-mimicking cryogel phantoms and a fresh excised human carotid artery. This adaptive method has been effectively proved to be accurate in a wider range of strains (0-7%) than commonly used gradient-based methods, and very adapted for investigating highly heterogeneous tissues. Resulting elastograms cover a wider range of strains (0-3.5%) than all previously reported intravascular elastograms, improving the discrimination between healthy and diseased regions.